Análisis de la calidad de los servicios de restauración de la Parroquia Malacatos, Cantón y Provincia de Loja. - Soto Andrade, Jheyson José (2023)
The work called Analysis of the quality of catering services in the Malacatos Parish, Canton and Province of Loja, had the objective of analyzing the quality of service offered by third category restaurants. In the first objective "To describe the tourist catering establishments in the Malacatos parish", the analysis of the environment was carried out through direct observation. A diagnostic matrix was prepared containing: general data on the restaurants, legal regulations and requirements, based on the methodology of the MINTUR, Food and Beverage Regulations. As a result, the restaurants complied with the requirements of the regulatory entities. For the second objective "To evaluate the quality of service of the catering establishments in the Malacatos parish"; the Servqual Model was applied, and the Likert scale from 1 to 5, with the objective of measuring the level of expectation and perceptions of the 350 clients surveyed, the data collection instrument had 29 questions: 7 general information questions and 22 questions from the Servqual Model, using 5 dimensions: tangible elements, empathy, safety, responsiveness and reliability. As a result, it was obtained that of the 5 dimensions contained in the Servqual model in the first restaurant. The SWOT matrix was elaborated with the determination of the internal and external factors, to develop the cross-SWOT matrix and set the strategic objectives. The third objective "To develop a strategic service improvement plan for the restaurant establishments". With the analysis of the results, it was proposed through an improvement plan to provide a solution to the problems found and thus improve quality and increase the level of customer satisfaction.